2000
DOI: 10.1093/emboj/19.16.4372
|View full text |Cite
|
Sign up to set email alerts
|

The eukaryotic mRNA decapping protein Dcp1 interacts physically and functionally with the eIF4F translation initiation complex

Abstract: Dcp1 plays a key role in the mRNA decay process in Saccharomyces cerevisiae, cleaving off the 5′ cap to leave an end susceptible to exonucleolytic degradation. The eukaryotic initiation factor complex eIF4F, which in yeast contains the core components eIF4E and eIF4G, uses the cap as a binding site, serving as an initial point of assembly for the translation apparatus, and also binds the poly(A) binding protein Pab1. We show that Dcp1 binds to eIF4G and Pab1 as free proteins, as well as to the complex eIF4E–eI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 47 publications
3
60
0
Order By: Relevance
“…Recent studies on the eIF4G-associated decapping enzyme Dcp1 in Saccharomyces cerevisiae have shown that eIF4E protects mRNA against degradation (27,28). One could speculate that phosphorylation of eIF4E would not only enhance initiation but also increase the susceptibility of the mRNA to decapping and subsequent degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on the eIF4G-associated decapping enzyme Dcp1 in Saccharomyces cerevisiae have shown that eIF4E protects mRNA against degradation (27,28). One could speculate that phosphorylation of eIF4E would not only enhance initiation but also increase the susceptibility of the mRNA to decapping and subsequent degradation.…”
Section: Discussionmentioning
confidence: 99%
“…In S. cerevisiae, the enzyme Dcp1 is a key protein in the decapping process during mRNA degradation (for a review on mRNA degradation see Tucker and Parker, 2000) and has recently been reported to interact with eIF4G (Vilela et al, 2000). This association occurs within the N-terminal domain of eIF4G but is very weak and by no means can compete with the eIF4E or PABP binding sites.…”
Section: Other Cellular Interacting Partnersmentioning
confidence: 99%
“…We previously reported that human Y14 interacts with the decapping complex and inhibits the activity of Dcp2 (22). The eukaryotic translation initiation factor 4E (eIF4E) competes with Dcp1 for binding to the cap structure and inhibits the decapping activity of Dcp2, whereby it prevents mRNA decay (19). Moreover, the cytoplasmic poly(A)-binding protein also inhibits Dcp2, suggesting that translation competes with mRNA decay (18).…”
mentioning
confidence: 99%